JZTX-V Targets the Voltage Sensor in Kv4.2 to Inhibit Ito Potassium Channels in Cardiomyocytes - Zhang, Yiya; Luo, Ji; He, Juan; Rong, Mingqiang; Zeng, Xiongzhi (Frontiers in Pharmacology, 2019)
Kv4 potassium channels are responsible for transient outward K+ currents in the cardiac action potential (AP). Previous experiments by our group demonstrated that Jingzhaotoxin-V (JZTX-V) selectively inhibits A-type potassium channels. However, the specific effects of JZTX-V on the transient outward (Ito) current of cardiomyocytes and underlying mechanism of action remain unclear. In the current study, 100 nM JZTX-V effectively inhibited the Ito current and extended the action potential duration (APD) of neonatal rat ventricular myocytes (NRVM). We further analyzed the effects of JZTX-V on Kv4.2, a cloned channel believed to underlie the Ito current in rat cardiomyocytes. JZTX-V inhibited the Kv4.2 current with a half-maximal inhibitory concentration (IC50) of 13 ± 1.7 nM. To establish the molecular mechanism underlying the inhibitory action of JZTX-V on Kv4.2, we performed alanine scanning mutagenesis of Kv4.2 and JZTX-V and assessed the effects of the mutations on binding activities of the proteins. Interestingly, the Kv4.2 mutations V285A, F289A, and V290A reduced the affinity for JZTX-V while I275A and L277A increased the affinity for JZTX-V. Moreover, mutation of positively charged residues (R20 and K22) of JZTX-V and the hydrophobic patch (formed by W5, M6, and W7) led to a significant reduction in toxin sensitivity, indicating that the hydrophobic patch and electrostatic interactions played key roles in the binding of JZTX-V with Kv4.2. Data from our study have shed light on the specific roles and molecular mechanisms of JZTX-V in the regulation of Ito potassium channels and supported its utility as a potential novel antiarrhythmic drug.